Impact of risk management strategies on the credit risk faced by commercial banks of Balochistan - Zia Ur Rehman; Noor Muhammad; Bilal Sarwar; Muhammad Asif Raz (Financial Innovation, 2019)
This study aims to identify risk management strategies undertaken by the commercial banks of Balochistan, Pakistan, to mitigate or eliminate credit risk. The findings of the study are significant as commercial banks will understand the effectiveness of various risk management strategies and may apply them for minimizing credit risk. This explanatory study analyses the opinions of the employees of selected commercial banks about which strategies are useful for mitigating credit risk. Quantitative data was collected from 250 employees of commercial banks to perform multiple regression analyses, which were used for the analysis. The results identified four areas of impact on credit risk management (CRM): corporate governance exerts the greatest impact, followed by diversification, which plays a significant role, hedging and, finally, the bank's Capital Adequacy Ratio. This study highlights these four risk management strategies, which are critical for commercial banks to resolve their credit risk.
Keywords: 650; Credit risk; Risk management strategies; Financial risk; Capital adequacy ratio; Hedging; Corporate governance; Diversification